Effect of DMSO on the catalytical production of 2, 5-bis(hydoxymethyl)furan from 5-hydroxymethylfurfural over Ni/SiO2 catalysts. Issue 1 (22nd October 2021) - Ojagh, Houman; Achour, Abdenour; Ho, Phuoc Hoang; Bernin, Diana; Creaser, Derek; Pajalic, Oleg; Holmberg, Johan; Olsson, Louise
Abstract : Highly effective production of 2, 5-bis(hydoxymethyl)furan (BHMF) from 5-hydroxymethylfurfural (HMF) has been achieved over Ni/SiO2 catalyst. An effect of DMSO on the HMF hydrogenation is demonstrated under practical conditions. Abstract : Hydroconversion of 5-hydroxymethylfurfural (HMF) to 2, 5-bis(hydoxymethyl)furan (BHMF) was studied over mono- and bimetallic supported catalysts. It was found that monometallic Ni/SiO2 catalysts exhibited superior performance with a total yield of BHMF of up to 99 wt%. This excellent performance may be attributed to higher Ni dispersion and low acidity of the support. Dimethyl sulfoxide (DMSO) is often present in HMF, due to the route used for its synthesis. DMSO adsorption caused a clear reduction of Ni/SiO2 performance for the HMF hydrodeoxygenation reaction. Characterization of the spent catalysts was performed using HAADF-STEM-EDX, Raman, ICP, and XPS spectroscopies, and showed the presence of sulfur and graphitic carbon, which could explain the deactivation.